LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR - Nur Hasanah; Luhur Wicaksono; Indri Astuti (Universitas Tanjungpura, 2019)
AbstractLearning discipline is an obedient attitude towards all regulations and is applied when learning activities take place. General problems in this study are: